An observational study of Yasmin® in the management of women with polycystic ovary syndrome. Issue 3 (1st July 2004) - Palep-Singh, Manisha; Mook, Karen; Barth, Julian; Balen, Adam
Abstract : Background: Polycystic ovary syndrome (PCOS) is the commonest endocrine disturbance affecting women in the reproductive age group and encompasses signs of hyperandrogenism, menstrual cycle disturbances and obesity. Some of the symptoms of PCOS may be ameliorated by the combined oral contraceptive pill (COCP). Methods: A pilot observational study was carried out in a university teaching hospital setting to determine whether the clinical and biochemical features of PCOS are ameliorated by a new COCP, Yasmin®, which contains a new progestogen, drosperinone. Treatment with Yasmin was given for 6 months to 17 patients. Results: Thirteen patients (76%) completed 6 months of therapy. Good cycle control was achieved in all patients. Percentage body fat increased, with no overall change in body mass index. Fasting insulin and triglyceride concentrations rose significantly. Serum total testosterone concentrations fell with a concomitant rise in sex hormone binding globulin levels. Hirsutism scores did not change significantly in the 12 women who were clinically hirsute. There was, however, a significant improvement in the acne scores. Four of the 17 patients dropped out of the trial between Cycles 3 and 5 due to side effects. Conclusions: Yasmin provides good cycle control for women with PCOS, with an improvement in acne over 6 months but not in other symptoms of the syndrome.